Analysis of Breastfeeding Self-Efficacy (BSE) in Breastfeeding Mothers - Etik Khusniyati; Heni Purwati (Kirana Publisher (KNPub), 2024)
Breast milk is the most ideal food for babies. Breast milk contains all the nutrients needed for growth and development and is sufficient until the baby is 6 months old. The 2018 Riskesdas results reported that exclusive breastfeeding coverage in 2018 was 37.3%. This is still far from the target of 80%. Breastfeeding self-efficacy (BSE) is one of the factors that influence the success of exclusive breastfeeding. The purpose of this study was to determine the factors associated with breastfeeding self-efficacy in breastfeeding mothers. This study is a quantitative research cross sectional design. The population was all mothers who had babies aged 0-6 months in Sumberejo Village, Mojosari District, Mojokerto Regency, totaling 34 respondents. The independent variables in this study were age, education, parity, occupation, knowledge and family support. The dependent variable in this study is breastfeeding self-efficacy. Data collection was carried out using instruments in the form of questionnaires and BSES-SF. Research analysis using the Spearman test. The statistical test results showed that there was a relationship between family support and breastfeeding self-efficacy with a p value of 0.032, while for other variables the p value> 0.05 was obtained so that there was no relationship between age, education, parity, occupation, and knowledge with breastfeeding self-efficacy. It is expected that health workers always motivate families to provide breastfeeding support to mothers